2022
DOI: 10.3390/antibiotics11101319
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Antibiotics in Primary Care Setting before and during COVID-19 Pandemic in Republic of Srpska, Bosnia and Herzegovina

Abstract: The pandemic of COVID-19 has brought many changes in health care systems at all levels of health care. The increase in the number of cases of COVID-19 has led to overuse and misuse of antibiotics.The aim of this study was to compare the consumption of antibiotics for systemic use in outpatients in the Republic of Srpska (RS), before and during the first year of the COVID-19 pandemic, as well as the association between antibiotic consumption and the rate of incidence and mortality of COVID-19. The total consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(35 reference statements)
2
4
0
Order By: Relevance
“…The year 2020 was marked by an enormous increase in the consumption of azithromycin both in outpatient and inpatient settings. These findings are similar to those reported from the surrounding areas and countries around the world ( ESAC-Net, 2022 ; Sokolović et al, 2022 ). An increase in the consumption of azithromycin could be partly explained due to its immunomodulatory and antiviral properties, in addition to its antibacterial effects ( Sultana et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The year 2020 was marked by an enormous increase in the consumption of azithromycin both in outpatient and inpatient settings. These findings are similar to those reported from the surrounding areas and countries around the world ( ESAC-Net, 2022 ; Sokolović et al, 2022 ). An increase in the consumption of azithromycin could be partly explained due to its immunomodulatory and antiviral properties, in addition to its antibacterial effects ( Sultana et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the months that followed, although knowledge about COVID-19 expanded significantly, the overlap of clinical and radiological features of COVID-19 with a bacterial infection of the respiratory tract helped to maintain the trend of increased and unnecessary antibiotic prescription. Numerous studies have reported an unjustified increase in antibiotic use during the COVID-19 pandemic, potentially accompanied by the rapid development and evolution of antibiotic resistance ( Rawson et al, 2020 ; Grau et al, 2021a ; Martinez-Guerra et al, 2021 ; Sokolović et al, 2022 ). Studies conducted so far show that the use of antibiotics in patients with COVID-19 greatly exceeds the number of proven bacterial superinfections ( Rawson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of the COVID-19 pandemic has led to increased number of hospitalized patients worldwide and to the overuse of antibiotics, resulting in further worsening of AMR [ 4 ]. In Bosnia and Herzegovina (B&H) before the COVID-19 pandemic, the consumption of AB expressed in defined daily dose per thousand inhabitants was higher than in the countries of Western Europe and this difference continued to increase during the COVID-19 pandemic [ 5 ]. Unlike many European countries where the consumption of AB decreased during the COVID-19 pandemic, an increase in the consumption of AB was observed in B&H, both in inpatient and outpatient settings [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Bosnia and Herzegovina (B&H) before the COVID-19 pandemic, the consumption of AB expressed in defined daily dose per thousand inhabitants was higher than in the countries of Western Europe and this difference continued to increase during the COVID-19 pandemic [ 5 ]. Unlike many European countries where the consumption of AB decreased during the COVID-19 pandemic, an increase in the consumption of AB was observed in B&H, both in inpatient and outpatient settings [ 5 , 6 ]. In addition to the excessive and often unjustified use of AB in human medicine, the use of these drugs in veterinary medicine, agriculture, and food production contributes to the development and spread of resistance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the elevated use of antibiotics in 2020 due to the coronavirus disease (COVID-19) pandemic and low AMR resilience in many countries, this number has potentially increased in recent years. Recently published data indicate that the mortality rate increased in COVID patients who received antibiotics [ 12 , 13 ]. A recent study based on metagenomic sequencing of 757 sewage samples from 243 cities in 101 countries suggested that certain geographies are more prone to transmission events and should receive additional attention [ 14 ].…”
Section: Introductionmentioning
confidence: 99%